The Effect of Supplementation on Pregnancy for Preventing Preeclampsia: A Literature Review - Anita Setyawati; Ermiati Ermiati; Yusshy Kurnia Herliani; Hasniatisari Harun (Padjadjaran Acute Care Nursing Journal, 2020)
Background: Preeclampsia increases maternal and perinatal morbidity and mortality. Previous studies found that vitamin D, L-arginine, folic acid, or phytonutrient in supplementation form play a role in reducing the incidence of preeclampsia. Objective: This study aimed to investigate the effect of supplementation on pregnancy for preventing preeclampsia.Method: The search strategy was conducted through CINAHL and Medline databases. Five hundred twenty-two articles were retrieved using ‘preeclampsia in pregnancy’ and ‘prevention’ keywords. Further, screening was carried out and resulted in 47 articles. In the end, five articles were included. To be eligible, the articles should be research articles, published from 2009-2019, and published in English.Results: This review found that vitamin D, L-arginine, and folic acid has the ability to prevent preeclampsia. Meanwhile, phytonutrient did not decrease the incidence of preeclampsia.Conclusion: Prescribing vitamin D, L-arginine, and folic acid to pregnant women is more likely to reduce the preeclampsia.Keywords: folic acid, L-arginine, phytonutrient, preeclampsia, vitamin D